Pengaruh variasi metode pengeringan terhadap karakteristik tepung ubi jalar ungu annealing - Gina Firgianti; Bambang Nurhadi; Marleen Sunyotodi (Composite : Jurnal Ilmu Pertanian, 2025)
Annealing purple sweet potato flour is a type of purple sweet potato flour processed using the annealing starch modification technique. The production of purple sweet potato flour involves a drying process, where the drying method significantly influences the final quality of the annealing purple sweet potato flour. The objective of this study was to determine the optimal drying method for producing annealing purple sweet potato flour with an intense purple color and high anthocyanin content, there by enhancing its physical appearance. The research employed a descriptive method followed by a difference test (t-test). The results indicated that the best drying method was sun drying, which produced purple sweet potato flour with the following characteristics: moisture content of 8.65%, anthocyanin content of 10,899.2 ppm, color intensity values of L 42.42, a* 27.88, and b* -9.02, initial gelatinization temperature of 75.56°C, peak viscosity of 417.75 cP, breakdown viscosity of 20 cP, and setback viscosity of 150.25 cP. Sun drying effectively preserved the deep purple color of the flour, resulting in an attractive appearance.